2015
DOI: 10.1177/0145721715604367
|View full text |Cite
|
Sign up to set email alerts
|

Talking About Type 2 Diabetes

Abstract: Efforts are needed to increase awareness and improve communication about T2DM risk factors, familial risk, and risk reduction behaviors within families with a family history of T2DM. Family members with and without T2DM should be encouraged to communicate with their relatives about T2DM and the risk to family members. Identification of family members who can facilitate communication, education, and modeling of healthy behaviors may increase awareness and motivate at-risk individuals to engage in risk-reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
2
7
0
1
Order By: Relevance
“…The evident identification processes within families also support the use of a family history approach to preventing worry and fear and motivating positive prevention outcomes. The present findings on intra-familial sharing of knowledge highlight the importance of focusing on issues concerning lack of perceived disease relevance, as described by Myers et al 12 …”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The evident identification processes within families also support the use of a family history approach to preventing worry and fear and motivating positive prevention outcomes. The present findings on intra-familial sharing of knowledge highlight the importance of focusing on issues concerning lack of perceived disease relevance, as described by Myers et al 12 …”
Section: Discussionsupporting
confidence: 80%
“… 9 11 A major obstacle to constructive intra-familial communication about prevention, familial risk and risk reduction behaviours is a lack of perceived disease relevance. 12 , 13 Godino et al 14 reported that people’s motivation to engage in risk-reducing health behaviours or to undergo screening is dependent on whether or not they are aware of their susceptibility to a given disease.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals at risk with a family history of diabetes may worry more about developing the disease, compared to those without diabetes in the family [43]. Furthermore, those with the most negative secondary experiences with type 2 diabetes can construct excessive cognitive and emotional responses to the disease [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, those with the most negative secondary experiences with type 2 diabetes can construct excessive cognitive and emotional responses to the disease [43]. Studies have shown that when health care providers have information and knowledge about a person’s family history of diabetes, this can have a temporary effect on behavioural changes in individuals at risk of type 2 diabetes [44].…”
Section: Discussionmentioning
confidence: 99%
“…In families where a member has T2D, relatives have a significantly higher risk of developing T2D themselves (Weijnen et al 2002;Khan et al 2003;Pierce et al 1995). A major obstacle to positive intra-familial communication about prevention, familial risk, and risk reduction is a lack of perceived disease relevance (Myers et al 2015;Heideman et al 2015). Motivation to engage in risk-reducing health behaviors or to undergo screening is dependent on awareness of one's susceptibility to a given disease (Godino et al 2014).…”
Section: Introductionmentioning
confidence: 99%